Continuous phase modulation for broadband satellite communications: design and trade‐offs. (26th March 2013) - Beidas, B. F.; Cioni, S.; De Bie, U.; Ginesi, A.; Iyer‐Seshadri, R.; Kim, P.; Lee, L. N.; Oh, D.; Noerpel, A.; Papaleo, M.; Vanelli‐Coralli, A.; Skinnemoen, Harald
SUMMARY In this paper, we introduce the continuous phase modulations mode of the second‐generation broadband satellite communications return link Digital Video Broadcast Interactive Satellite System standard. Starting from a detailed discussion about the impairments faced in a typical broadband satellite system user set‐up, we introduce the waveform selection rationale, the design trade‐offs, and the waveform performance under realistic system assumptions. We show that the designed continuous phase modulations mode exhibits an excellent trade‐off between performance and robustness to nonlinear distortions at low and medium spectral efficiency thus suggesting its adoption for the consumer market profile of the Digital Video Broadcast Interactive Satellite System. Copyright © 2013 John Wiley & Sons, Ltd.